Histochemical differentiations of the spinal motor neurons during mouse embryogenesis - AR.Fazel (Ph.D); MR.Nikravesh (Ph.D); M.Jalali (Ph.D) (مجله دانشگاه علوم پزشکی گرگان, 2003)
Background & Objective: The pattern of cell types in vertebrate embryos depend on the function of organizing centers, specialized cell groups that direct the fate of nearby cells through the secretion of inductive factors. Our previous studies showed that during early neural tube formation, the notochord is essential for the induction of ectoderm and for the subsequent differentiations of the neuroepithelium. It is well known that glycoconjugates are developmentally regulated expression on the surfaces of early embryonic cells and could therefore be involved in many critical morphogenetic and histogenetic events during embryonic development. Materials & Methods: In the present study, histochemical studies were carried out to detect the presence and distribution of terminal sugars during development of precursors of motor neurons within the developing spinal cord in balb/c mice. Embryos from day 9 to 14 of gestation were fixed and processed for lectin histochemical studies by using horseradish peroxidase labeled WFA with binding specificity for terminal N-acetylgalactosamine. Results: The first reaction was occurred weakly on the cells surface and extra cellular matrix just around the peripheral portion of floor plate on day 13 of gestation. It seems that these cells are developing premotor neurons, which will form the future motor neurons of the spinal cord. The reaction increased significantly and extended to the deep part of spinal floor plate by day 14. Conclusion: These data indicate that glycoconjugates containing N-acetylgalactosamine may play important roles in differentiation of the floor plate motor neuron and perhaps glia cells in final development of the ventral part of the spinal cord.